2020
DOI: 10.1039/d0ra01436b
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4-ethylenedioxyselenophene): effect of solvent and electrolyte on electrodeposition, optoelectronic and electrochromic properties

Abstract: In this article, we report the effect of electropolymerization conditions such as solvent and supporting electrolyte on the redox, optoelectronic and electrochromic properties of PEDOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…PEDOT is often spin‐coated with polystyrene sulfonate (PSS) to form PEDOT:PSS, [ 8,9 ] but PEDOT thin films can also be fabricated by electropolymerization, [ 10,11 ] in situ chemical polymerization, [ 12–15 ] vapor phase polymerization (VPP), [ 16–19 ] and oxidative chemical vapor deposition (oCVD). [ 20–26 ] For PEDOT, the highest value of σ to date, 8797 ± 1178 S cm −1 , was reported by Cho et al.…”
Section: Introductionmentioning
confidence: 99%
“…PEDOT is often spin‐coated with polystyrene sulfonate (PSS) to form PEDOT:PSS, [ 8,9 ] but PEDOT thin films can also be fabricated by electropolymerization, [ 10,11 ] in situ chemical polymerization, [ 12–15 ] vapor phase polymerization (VPP), [ 16–19 ] and oxidative chemical vapor deposition (oCVD). [ 20–26 ] For PEDOT, the highest value of σ to date, 8797 ± 1178 S cm −1 , was reported by Cho et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LiBF 4 (lithium tetrafluoroborate), TBABF 4 (tetra-nbutylammonium tetrafluoroborate), TBAClO 4 (tetra-n-butylammonium perchlorate), TBAPF 6 (tetra-nbutylammonium hexafluorophosphate), LiClO 4 (lithium perchlorate), etc. have been used as supporting electrolytes [39][40][41][42].…”
Section: Methods Of Synthesis Of π-Conjugated Polymersmentioning
confidence: 99%
“…Surface modification of neural electrodes with nanostructured conductive materials can create a large active surface area, which enables neural recording/stimulation with exceptional spatiotemporal resolution and provides multiple channels of electrical, chemical, and mechanical information at the subcellular level. , However, direct polymerization of conductive polymers from aqueous solution using Cl – , ClO 4 – , tetrafluoroborate (TFB), or sodium poly­(styrene sulfonate) (PSS) as the dopant usually generates compact polymer films with limited active surface area. To produce nanostructured conductive polymers, rigid or soft templates are usually required, which adds up the complicity of electrode fabrication and chance to incorporate unwanted chemicals. , The nature of the solvent has a great effect on the morphology, conductivity, electrolytic activity, and other chemical/physical properties of the electrochemically synthesized polymers. , Due to the low solubility of 3,4-ethylenedioxythiophene (EDOT) in aqueous solution, organic solvents are frequently used to dissolve EDOT for the preparation of PEDOT coatings. , Chiang et al found that better electrical conductivity, electroactivity, and reversibility of ionic transfer could be obtained when a high-polarity solvent (dimethyl sulfoxide, DMSO), which enhances charge hopping in the polymer, was used during the polymerization of EDOT . Many studies have shown that conductive polymer films prepared from dichloromethane, a solvent having similar polarity to DMSO, exhibit a much rough surface with clusters of granules in a micrometer scale, no matter what kind of supporting electrolyte is used, while those prepared from water, propylene carbonate, ionic liquid, or other common solvents showed more compact and flat morphology. ,,, Besides the solvent, the supporting electrolyte also affects the morphology, electroactivity, stability, and the electrochromic features of conductive polymers.…”
Section: Introductionmentioning
confidence: 99%